CIC Mutation as a Molecular Mechanism of Acquired Resistance to Combined BRAF‐MEK Inhibition in Extramedullary Multiple Myeloma with Central Nervous System Involvement. (18th October 2019) - Da Vià, Matteo Claudio; Solimando, Antonio Giovanni; Garitano‐Trojaola, Andoni; Barrio, Santiago; Munawar, Umair; Strifler, Susanne; Haertle, Larissa; Rhodes, Nadine; Teufel, Eva; Vogt, Cornelia; Lapa, Constantin; Beilhack, Andreas; et al.
Abstract: Combined MEK‐BRAF inhibition is a well‐established treatment strategy in BRAF ‐mutated cancer, most prominently in malignant melanoma with durable responses being achieved through this targeted therapy. However, a subset of patients face primary unresponsiveness despite presence of the activating mutation at position V600E, and others acquire resistance under treatment. Underlying resistance mechanisms are largely unknown, and diagnostic tests to predict tumor response to BRAF‐MEK inhibitor treatment are unavailable. Multiple myeloma represents the second most common hematologic malignancy, and point mutations in BRAF are detectable in about 10% of patients. Targeted inhibition has been successfully applied, with mixed responses observed in a substantial subset of patients mirroring the widespread spatial heterogeneity in this genomically complex disease. Central nervous system (CNS) involvement is an extremely rare, extramedullary form of multiple myeloma that can be diagnosed in less than 1% of patients. It is considered an ultimate high‐risk feature, associated with unfavorable cytogenetics, and, even with intense treatment applied, survival is short, reaching less than 12 months in most cases. Here we not only describe the first patient with an extramedullary CNS relapse responding to targeted dabrafenib and trametinib treatment, we furthermore provide evidence that a point mutation within the capicua transcriptional repressor (CIC) gene mediated the acquired resistance in this patient. Key Points: BRAF mutations constitute an attractive druggable target in multiple myeloma. This is the first genomic dissection of the central nervous system involvement in a multiple myeloma patient harboring a druggable BRAF V600E mutation. Deep genomic characterization of the extramedullary lesion prompted a personalized therapeutic approach. Acquisition of CIC mutation confers a mechanism of BRAF‐MEK inhibitor drug resistance in multiple myeloma. The in silico interrogation of the CoMMpass clinical study revealed 10 patients with somatic mutations of CIC and its downregulation at gene expression level in multiple myeloma. CIC gene silencing decreases the sensitivity of multiple myeloma cells to BRAF‐MEK inhibition in vitro. The correlation between CIC downregulation and ETV4/5 nuclear factor expression in multiple myeloma BRAF ‐mutant cells is shown for the first time. CIC mutation, its downregulation, and the related downstream effect on MMP24 support disseminative potential providing new clues in the extramedullary biology definition. Abstract : This article presents a case report of a patient with multiple myeloma (MM) and extramedullary localization at the central nervous system (CNS) at relapse. This is the first genomic characterization of CNS MM localization and provides evidence that a point mutation within the CIC gene is a possible mechanism of acquired resistance.